Safety‐net hospitals versus non‐safety centers and clinical outcomes after trans‐catheter aortic valve replacement. Issue 3 (18th July 2020) - Sheikh, Muhammad Adil; Deo, Salil V.; Riaz, Haris; Raza, Sajjad; Altarabsheh, Salah E.; Wilson, Brigid; Elgudin, Yakov; Cmolik, Brian; Pelletier, Marc; Markowitz, Alan H.
Abstract: Objective: To compare post‐procedural outcomes of trans‐catheter valve replacement (TAVR) among safety‐net (SNH) and non‐safety net hospitals (non‐SNH). Background: SNH treat a large population of un‐insured and low income patients; prior studies report worse outcome at these centers. Results of TAVR at these centers is limited. Methods: Adults undergoing TAVR at hospitals in the US participating in the National In‐patient sample (NIS) database from January 2014 to December 2015 were included. A 1:1 propensity‐matched cohort of patients operated at SNH and non‐SNH institutions was analyzed, on the basis of 16 demographic and clinical co‐variates. Main outcome was all‐cause post‐procedural mortality. Secondary outcomes included stroke, acute kidney injury and length of post‐operative stay. Results: Between 2014 and 2015, 41, 410 patients (mean age 80 ± 0.11 years, 46% female) underwent TAVR at 731 centers; 6, 996 (16.80%) procedures were performed at SNH comprising 135/731 (18.4%) of all centers performing TAVR. SNH patients were more likely to be female (49% vs. 46%, p < .001); admitted emergently (31% vs. 21%; p < .001; at the lowest quartile for household income (25% % vs. 20%; p < .001) and from minorities (Blacks 5.9% vs. 3.9%; Hispanic 7.2% vs. 3.2%).Adjusted logistic regression was performed on 6, 995 propensity‐matched patient pairs. Post‐procedural mortality [OR 0.99(0.98–1.007); p = .43], stroke [OR 1.009(0.99–1.02); p = .08], acute kidney injury [OR 0.99(0.96–1.01); p = .5] and overall length of stay (6.9 ± 0.1 vs. 7.1 ± 0.2 days; p = .57) were comparable in both cohorts. Conclusion: Post‐procedural outcomes after TAVR at SNH are comparable to national outcomes and wider adoption of TAVR at SNH may not adversely influence outcomes.